2020
DOI: 10.1186/s12940-020-00672-0
|View full text |Cite
|
Sign up to set email alerts
|

In utero and peripubertal metals exposure in relation to reproductive hormones and sexual maturation and progression among boys in Mexico City

Abstract: Background Endocrine disrupting chemicals (EDCs) such as metals have been reported to alter circulating reproductive hormone concentrations and pubertal development in animals. However, the relationship has rarely been investigated among humans, with the exception of heavy metals, such as Pb and Cd. Our aim was to investigate measures of in utero and peripubertal metal exposure in relation to reproductive hormone concentrations and sexual maturation and progression among boys from the Early Lif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…Interest in pubertal alterations has been boosted by recent epidemiological reports of disturbed puberty onset in humans, which may be related to EDC exposure or food nutrition. As early as 1998, Ashby and Tinwell suggested that subcutaneous injections of 600 and 800 mg/kg BPA could induce premature VO in rats . Later, other groups also reported early VO age in rats treated with BPA perinatally or postnatally. , The dosage chosen in the above studies was higher than that in environmental exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in pubertal alterations has been boosted by recent epidemiological reports of disturbed puberty onset in humans, which may be related to EDC exposure or food nutrition. As early as 1998, Ashby and Tinwell suggested that subcutaneous injections of 600 and 800 mg/kg BPA could induce premature VO in rats . Later, other groups also reported early VO age in rats treated with BPA perinatally or postnatally. , The dosage chosen in the above studies was higher than that in environmental exposure.…”
Section: Discussionmentioning
confidence: 99%